2017
DOI: 10.3892/mco.2017.1436
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine phosphorylase expression and prognosis in colorectal cancer treated with 5‑fluorouracil‑based chemotherapy: A meta‑analysis

Abstract: In the past decades, various studies have suggested a possible link between thymidine phosphorylase (TP) level and colorectal cancer (CRC) treated with 5-fluorouracil (5-FU)-based chemotherapy; however, they have arrived at inconsistent results. Therefore, the present meta-analysis aimed to disclose a more comprehensive evaluation of this relationship. PubMed, the Cochrane Library, Ovid MEDLINE, Embase and China National Knowledge Infrastructure were systematically searched for studies that evaluated the progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…However, high TP expression in tumor tissue may increase concentration of 5-FU in cancer tissues thorough angiogenesis and may contribute to the sensitivity of the DPD inhibitor through promoting phosphorylation of 5-FU. Recent meta-analysis indicated that low TP expression was associated with poor prognosis in 5-FU-based adjuvant chemotherapy (28). Consistent with this, our findings suggest that patients with low levels of TP mRNA in primary tumours had worse RFS than those with high levels of TP when adjuvant chemotherapy with oral fluoropyrimidine was administered.…”
Section: Discussionsupporting
confidence: 88%
“…However, high TP expression in tumor tissue may increase concentration of 5-FU in cancer tissues thorough angiogenesis and may contribute to the sensitivity of the DPD inhibitor through promoting phosphorylation of 5-FU. Recent meta-analysis indicated that low TP expression was associated with poor prognosis in 5-FU-based adjuvant chemotherapy (28). Consistent with this, our findings suggest that patients with low levels of TP mRNA in primary tumours had worse RFS than those with high levels of TP when adjuvant chemotherapy with oral fluoropyrimidine was administered.…”
Section: Discussionsupporting
confidence: 88%
“…The relationship between their activity and the sensitivity of CRC to 5-FU has been demonstrated in several studies. Higher expression of TP, UP and OPRT levels displayed enhanced sensitivity to 5-FU therapy[ 10 - 12 ]. Similarly, as DPD contributes to the degradation of 5-FU, its expression level was inversely correlated with chemosensitivity[ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although 5-FU-based chemotherapies benefit colon cancer patients, a large fraction of them relapse [28] , [29] . Chemo-resistance and metastasis remain a major problem in cancer treatment [30] , [31] .…”
Section: Discussionmentioning
confidence: 99%